Low-Carbon Operation Decision of Green Packaging Supply Chain Considering Production and Marketing Cooperation - Peng, Jing; Shi, Yutong (International Journal of Industrial Engineering: Theory, Applications and Practice, 2025)
Given the cooperative nature of the production and marketing segments of the supply chain, this paper investigates the manufacturer’s low-carbon traceable production and the distributor’s low-carbon marketing strategies in a manufacturer-led secondary supply chain under a carbon cap-and-trade policy. The paper proposes the pass-contract model to enhance the cooperative nature of supply chain actors and constructs four Stackelberg game models. The study shows that both low-carbon marketing strategies by distributors and the introduction of traceability technologies by manufacturers can increase the profits of supply chain actors; the sensitivity coefficient of traceability and the sensitivity coefficient of marketing efforts at the brand end positively correlate with the profits of manufacturers and distributors. Under the cost-sharing model, when the share ratio is within a reasonable range, it not only leads to the highest level of carbon emission reductions (CER) in the supply chain but also maximizes supply chain profits. Adopting green packaging strategies, such as cost-sharing contracts, production and sales balancing, traceability technology, and low-carbon marketing, is essential for supply chain members to achieve sustainable development and environmental benefits.